Effectiveness of Neuropediatric Inpatient Rehabilitation - Stadler, Hannah; Müller, Kristina; Kurlemann, Gerhard; Lendt, Michael (Neuropediatrics, 2023)
Aim Inpatient rehabilitation plays an important role in treating neurological diseases in children and adolescents. However, there is a lack of current research concerning this matter. This retrospective study aims to analyze the effectiveness of neuropediatric inpatient rehabilitation, to identify influencing factors, and to examine the importance of inpatient rehabilitation programs.Methods We reviewed medical records of patients, diagnosed with cerebral palsy, traumatic brain injury (TBI), or stroke who had an inpatient rehabilitation at the Department of Neuropediatrics of St. Mauritius Therapieklinik in Meerbusch from 2012 to 2019. The patients received several units of different therapies such as motor and cognitive rehabilitation or speech therapy per day, depending on their individual needs and aims. Rehabilitation outcome was assessed by comparing Gross Motor Function Measure-88 and Pediatric Evaluation of Disability Inventory admission and discharge scores. Influences of sex, age, length of stay (LOS), and admission score were analyzed.Results A total of 738 patients with a mean age of 9.2 (± 5.1) years and a mean LOS of 53.8 (± 33.7) days were included; 38.5% were female. Patients, regardless of their diagnosis, sex, or age, demonstrated highly significant and meaningful improvements of self-care, mobility, and social function during inpatient rehabilitation. Especially, the group of patients with TBI and stroke could approximate their skills substantially to the ones of healthy peers. A longer LOS correlated significantly with greater improvement of skills.Interpretation This is a current study, supporting the effectiveness of neuropediatric inpatient rehabilitation and affirming its value in treating neurological diseases in children and adolescents.
Keywords: rehabilitation; neuropediatric; outcome; cerebral palsy; traumatic brain injury; stroke